PESTAL: uma análise das variáveis macroambientais e suas relações com indicadores setoriais de retorno do investimento - Tempesta, Verônica Rosa (2020)
The influence of the macroenvironment on the Return on Investment of companies from different sectors is a major factor for decision making. The objective of this research was to investigate the existing connections between the macroenvironmental variables, recommended by PESTAL, the sectoral indicators of Return on Investment (ROCE) and also the sectoral indicators of Company Value / Invested Capital (VE / CI). In a complementary way, it was sought to analyze whether the sectorial Return on Investment indicators behave according to the fluctuations of economic cycles. To carry out the study, data from the sectors categorized according to the Assaf Neto Institute were observed, considering the period from 2000 to 2018. The analysis was performed using: distance technique DP2 to calculate the constructs of PESTAL; Multiple Linear Regressions for the connections between the macroenvironment and the independent variables ROCE and VE / CI; and Kruskal-Wallis median test to analyze cyclical oscillations. The results confirmed that there is a connection between the macroenvironment and the sectoral indicators of investment returns. In relation to ROCE, there are significant correlations between the following sectors and constructs of PESTAL: Water and Sewage (IFRS); Food and Beverage (economical); Cements and Aggregates (social, technological and legal); General trade (political, technological, environmental and legal); Transport Concessionaire (legal); Appliances (social); Electric Energy (social, technological and legal); Oil Extraction and Distribution (IFRS); Leisure, Culture and Entertainment (social, technological and legal); Machines (economic and legal); Mining (social); Metals (technological); Pulp and Paper (political, technological, environmental and IFRS); Basic Chemistry (IFRS); Diversified Chemistry (political); Retail Special Lines (economic); and Clothing (political, economic and IFRS). In relation to VE / CI, there are significant correlations between the following sectors and constructs of PESTAL: Steel (social, technological and legal); Food and Beverages (social); Shoes (political); Cements and Aggregates (political, social and IFRS); General trade (political); Civil Construction (political, technological and IFRS); Appliances (economical); Oil Extraction and Distribution (IFRS); Miscellaneous Materials Industries (economic); Perfumery and Cosmetics (IFRS); Pulp and Paper (technological); Telecommunications Services (economic, technological and environmental); and Retail Special Lines (political and IFRS). Of the total, 17 sectors showed some connection between macroenvironment (PESTAL) and ROCE and 13 sectors, between macroenvironment and VE / CI. It was also observed that the ROCE and VE / CI indicators showed significant differences in some phases of the economic cycles. Specifically, the ROCE showed medians of 10.4% in the recovery phases, 13% in the recession and 9.7% in the contraction. The VE / CI presented a median of 0.86 in expansion, 0.31 in recovery and 0.62 in contraction. These differences are consistent with the literature, since the cycles consist of variations that end up affecting sectors of the economy. In addition, it was observed that the sectors Construction, Leisure, Culture and Entertainment and Mining present significant differences in the phases of the economic cycles for the ROCE, showing that the effects of the Economic Cycles occur with greater intensity in these sectors. Given these results, managers, investors and creditors need to be aware of external influences in these sectors in their decision-making processes. In addition, government representatives can consider the results obtained in the implementation of public policies, as some sectors are substantially more affected than others due to the dimensions of PESTAL.